Single-Dose Pharmacokinetics of Indinavir and the Effect of Food - Yeh, Kuang C. (American Society for Microbiology, 1998)
Indinavir sulfate is a human immunodeficiency virus type 1 (HIV-1) protease inhibitor indicated for treatment of HIV infection and AIDS in adults. The purpose of this report is to summarize single-dose studies which characterized the pharmacokinetics of the drug and the effect of food in healthy volunteers. Indinavir concentrations in plasma and urine were obtained by high-pressure liquid chromatography and UV detection assay methods. The results indicate that indinavir was rapidly absorbed in the fasting state, with the time to the maximum concentration in plasma occurring at ∼0.8 h for all doses studied. Over the 40- to 1,000-mg dose range studied, concentrations in plasma and urinary excretion of unchanged drug increased greater than dose proportionally. The nonlinear pharmacokinetics were attributed to the dose-dependent oxidative metabolism of first-pass metabolism as well as to metabolism in the systemic circulation. Renal clearance slightly exceeded the glomerular filtration rate, suggesting a net tubular secretion component. At high concentrations in plasma, tubular secretion appeared to be lowered because there was a trend for a decreased renal clearance. Administration of 400 mg of indinavir sulfate following a high-fat breakfast resulted in a blunted and decreased absorption (areas under the concentration-time curves [AUCs], 6.86 μM·h in the fasted state versus 1.54 μM·h in the fed state; n = 10). However, two types of low-fat meals were found to have no significant effect on the absorption of 800 mg of indinavir sulfate (AUCs, 23.15 μM·h in the fasted state versus 22.71 and 21.36 μM·h, respectively, in the fed state; n = 11). Immediately following dosing, the concentrations of indinavir in urine often exceeded its intrinsic solubility. To reduce the risk of nephrolithiasis, it is recommended that indinavir sulfate be administered with water.